2018
DOI: 10.1158/1078-0432.ccr-17-2656
|View full text |Cite
|
Sign up to set email alerts
|

Induction Chemotherapy plus Concurrent Chemoradiotherapy in Endemic Nasopharyngeal Carcinoma: Individual Patient Data Pooled Analysis of Four Randomized Trials

Abstract: Because of the uneven geographic distribution and small number of randomized trials available, the value of additional induction chemotherapy (IC) to concurrent chemoradiotherapy (CCRT) in nasopharyngeal carcinoma (NPC) remains controversial. This study performed an individual patient data (IPD) pooled analysis to better assess the precise role of IC + CCRT in locoregionally advanced NPC. Four randomized trials in endemic areas were identified, representing 1,193 patients; updated IPD were obtained. Progressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 31 publications
4
104
0
Order By: Relevance
“…Increasing evidence suggests that systemic induction chemotherapy (IC) can effectively eliminate NPC micrometastasis and ultimately improve patient survival [18][19][20]. However, the responses to chemotherapy are heterogeneous, and some patients can develop resistance, leading to treatment failure [20].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that systemic induction chemotherapy (IC) can effectively eliminate NPC micrometastasis and ultimately improve patient survival [18][19][20]. However, the responses to chemotherapy are heterogeneous, and some patients can develop resistance, leading to treatment failure [20].…”
Section: Introductionmentioning
confidence: 99%
“…By lowering tumor volume and restricting occult micrometastasis, induction chemotherapy (IC) before RT has been proposed to further decrease distant metastasis risk. Previous studies have shown that IC might improve survival outcomes in patients with locoregionally advanced NPC (7,8). Nevertheless, not all patients with locoregionally advanced NPC benefit from IC.…”
Section: Introductionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC) is a squamous epithelial cell carcinoma with an incidence of 15‐50 cases per 100 000 and is especially prevalent in Southeast Asia . Currently, with the application of intensity‐modulated radiotherapy, the locoregional control rate of NPC is much higher than before .…”
Section: Introductionmentioning
confidence: 99%